Profile of patients with rheumatic diseases undergoing treatment with anti-TNF agents in the Brazilian Public Health System (SUS), Belo Horizonte - MG - Haliton Alves de Oliveira Junior; Alessandra Maciel Almeida; Francisco Assis Acurcio; Jéssica Barreto dos Santos; Adriana Maria Kakehasi; Juliana Alvares; Clarice Gomes e Souza Dabés; Mariangela Leal Cherchiglia (Universidade de São Paulo, 2015)
The aim of this study was to describe the baseline demographic and clinical characteristics as well as the functional status of a prospective cohort of patients with rheumatic diseases assisted by the Brazilian Public Health System (SUS). Data for 302 patients receiving tumor necrosis factor α inhibitors (anti-TNF agents) was collected through a standard form. Among patients, 229 (75.8%) were female and 155 (51.3%) were Caucasian; the mean age was 50.3 ± 12.8 years, and the mean disease duration was 9.9 ± 8.7 years. Among them 214 patients (70.9%) received adalimumab, 72 (23.8%) etanercept, and 16 (5.3%) infliximab. Mean Health Assessment Questionnaire-Disability Index (HAQ-DI) was 1.37 ± 0.67 for all participants. Poor functional response was associated with female gender, married patients and with a score of < 0.6 on the EuroQoL-5 dimensions (EQ-5D). Significant correlation was found between the HAQ-DI values, disease activity and quality of life (QOL). The results obtained in this study contribute to a better understanding of the clinical and demographic characteristics of patients with rheumatic diseases at the beginning of anti-TNF-agent treatment by SUS. Furthermore, our findings are consistent with another Brazilian and foreign cross-sectional investigations. This knowledge can be of great importance for further studies evaluating the effectiveness of biological agents, as well as, to contribute to improve the well-being of the patients with rheumatic diseases.